2011
DOI: 10.1248/bpb.34.1566
|View full text |Cite
|
Sign up to set email alerts
|

Sauchinone Suppresses Pro-inflammatory Mediators by Inducing Heme Oxygenase-1 in RAW264.7 Macrophages

Abstract: Heme oxygenase-1 (HO-1) is a rate-limiting enzyme in heme catabolism responsible for catalyzing the split of free heme into carbon monoxide (CO), free iron and biliverdin/bilirubin. 1) Recent studies have shown that HO-1 has proven involvment in the resolution of inflammatory responses.2) HO-1 and its enzymatic by-products are the critical regulators of inflammation predominantly targeted against macrophages.3) Studies have shown that the anti-inflammatory action of HO-1 is mediated by inhibition of the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The use of specific inhibitors for MAPK pathways confirms the involvement of ERK pathway, but not of JNK pathway, in the anti-inflammatory action of ME. These data are in good agreement with other reports that numerous compounds, both natural and man-made ones, inhibit proinflammatory mediators through upregulation of HO-1 and ERK signaling [3335]. …”
Section: Discussionsupporting
confidence: 93%
“…The use of specific inhibitors for MAPK pathways confirms the involvement of ERK pathway, but not of JNK pathway, in the anti-inflammatory action of ME. These data are in good agreement with other reports that numerous compounds, both natural and man-made ones, inhibit proinflammatory mediators through upregulation of HO-1 and ERK signaling [3335]. …”
Section: Discussionsupporting
confidence: 93%
“…33 Jeong et al 34 also showed that sauchinone, an active lignan isolated from the roots of S. chinensis, upregulated HO-1 expression through the p38 MAPK-Nrf2/ARE-dependent pathway in t-butyl hydroperoxide-damaged HepG2 cells. However, Li et al 9 found that sauchinone induced HO-1 expression via the ERK pathway in LPS-stimulated RAW264.7 cells but did not affect the p38 MAPK and JNK pathways. The differences in the results can be attributed to the extract preparation method, the plant part used for extraction, and differences in experimental conditions (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, sauchinone, a biologically active compound isolated from the root of S. chinensis, inhibits pro-inflammatory responses through HO-1-mediated anti-inflammatory effects of S. chinensis aerial parts 403 .......................................................................................................................... increased HO-1 expression via the ERK pathway. 9 However, the anti-inflammatory activity of the aerial parts of S. chinensis, and the cellular and molecular mechanisms involved (besides the ERK pathway) have not yet been determined. In the present study, we showed that the aerial parts of S. chinensis also inhibit LPS-induced proinflammatory mediators, activate p38 and Akt pathways, lead to nuclear translocation of NF-kB and Nrf2, and induce phosphorylation of the STAT1/3 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPKs are a group of serine/threonine protein kinases that are activated in response to diverse extracellular stimuli that mediate signal transduction from the cell surface to the nucleus [22]. MAPKs have been implicated in the signaling pathway relevant to LPS-induced inflammations.…”
Section: Discussionmentioning
confidence: 99%